The prevalence of onchocerciasis-associated epilepsy in Mundri West and East Counties, South Sudan: A door-to-door survey - Jada, SR; Dusabimana, A; Abd-Elfarag, G; Okaro, S; Brusselaers, N; Carter, JY; Logora, MY; Rovarini, JM; Newton, CR; Colebunders, R (MDPI, 2022)
A two-phase survey of epilepsy was conducted in selected villages in Mundri West and East Counties (26 June–8 July, 2021), an onchocerciasis-endemic area in Western Equatoria State in South Sudan. In the first phase, households were visited by a trained research team to identify persons suspected to have epilepsy. In the second phase, persons suspected to have epilepsy were interviewed and examined by a clinician to confirm the diagnosis. A total of 364 households agreed to participate in the survey, amounting to 2588 individuals. The epilepsy screening questionnaire identified 91 (3.5%) persons with suspected epilepsy, of whom the diagnosis of epilepsy was confirmed by a clinician in 86 (94.5%). The overall prevalence of confirmed epilepsy was 3.3% (95% CI: 2.7–4.1%), and of nodding syndrome was 0.9% (95% CI: 0.6–1.4%). In 61 (16.8%) households there was at least one person with epilepsy. Only 1212 (46.9%) of 2583 people took ivermectin during the last distribution round in 2021. The annual epilepsy incidence was 77.3/100,000 (95% CI: 9.4–278.9/100,000) and the annual epilepsy mortality was 251.2/100,000 (95% CI: 133.8–428.7/100,000). In conclusion, a high prevalence and incidence of epilepsy was observed in villages in Mundri. Urgent action is needed to prevent children from developing onchocerciasis-associated epilepsy by strengthening the local onchocerciasis-elimination programme.